(3eYLe GdHdOGf aj eYQaI GdeOf hGdbQi hGdNQGH hGdYeGQ hGdSgd hGdhYQ ef cd ecGfs - (3jGbhJ Hf YHO Gddg GdQhej GdMehj, TgGH GdOjf CHh YHO Gddg,J (B626 (3g` s
(3ChdgG (B:s
(3HGH GdLje hGdaGA (B( (3GdLaGQ (B) s
(3BNQgG (B:s
(3GdShOI s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B131 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B178s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B23 - (3U (B566 s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi (B(1165) s
Keywords: (3GdLZQGajG h GdHdOGfs